2013
DOI: 10.1002/cctc.201300724
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Catalytic Activity of Platinum Nanoparticles by Exfoliated Metal Hydroxide Nanosheets

Abstract: A novel 2-dimensional catalytic system was developed in which platinum nanoparticles (Pt NPs) were immobilized on exfoliated MgAl-layered double hydroxide (LDH) nanosheets through an electrostatic self-assembly between negatively charged Pt NPs and positively charged LDH nanosheets. The LDH nanosheets effectively provided the large double sides of hydroxide functionality to absorb the Pt NPs, as well as fast diffusion rates of the incoming reactants into catalyst surfaces. This new nanostructure improved the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…LDH materials have been widely used as catalyst supports. The structure LDH materials (e.g., 2D surface area, flexible composition, confinement effect) allow a series of supported noble metal (Ru, Pd, Pt, and Au) catalysts to be prepared; the metal particles in these materials have a high degree of dispersity, as well as structural stability resulting from the strong anchoring effect of the support. The presence of surface hydroxyl groups and defect structures (e.g., oxygen vacancies) located in the brucite‐like host layers can significantly influence the particle size, morphology, and electronic structure of the supported metal catalysts.…”
Section: Ldhs As Catalysts Supportsmentioning
confidence: 99%
“…LDH materials have been widely used as catalyst supports. The structure LDH materials (e.g., 2D surface area, flexible composition, confinement effect) allow a series of supported noble metal (Ru, Pd, Pt, and Au) catalysts to be prepared; the metal particles in these materials have a high degree of dispersity, as well as structural stability resulting from the strong anchoring effect of the support. The presence of surface hydroxyl groups and defect structures (e.g., oxygen vacancies) located in the brucite‐like host layers can significantly influence the particle size, morphology, and electronic structure of the supported metal catalysts.…”
Section: Ldhs As Catalysts Supportsmentioning
confidence: 99%
“…The lateral (10true1¯0) facet with a high density of dangling bonds may have relatively active chemical characteristics, resulting in the preferential deposition of Au NPs on the (10true1¯0) facet. Most recently, Jung et al reported the synthesis of Pt nanoparticles immobilized on exfoliated MgAl‐LDH nanosheets via an electrostatic self‐assembly between negatively‐charged Pt NPs and positively‐charged LDH nanosheets ( Figure ). The LDH nanosheets provide double sides of hydroxide functionality to stabilize Pt NPs, and facilitate a fast diffusion of reactants into the catalyst surface.…”
Section: Ldh‐based Heterogeneous Catalystsmentioning
confidence: 99%
“…MMOs层板表面高度分散的负载型金属催化剂. 2002 年, Choudary等 [56] 基于LDHs层间的几何限域作用, 将 [60] Jung等 [62] [60] (网络版彩图) 图 13 LBL法制备Au/ZnAl-LDH薄膜催化剂示意图 [61]…”
Section: 催化剂对高温生长碳纳米管表现了更好的催化性能unclassified